World catalog of extant and fossil Corethrellidae (Diptera) - Borkent, Art (Zootaxa, 2014)
A world catalog of extant and fossil frog-biting midges (Diptera: Corethrellidae) provides full type information, known life stages, and distribution of each species. There are 105 extant and seven fossil species of Corethrellidae but unnamed species are known from Costa Rica, Colombia and Madagascar. New information on types and other important specimens are provided.